PERLINDUNGAN HUKUM PEMEGANG CEK KOSONG - Dwi Tatak Subagiyo (Perspektif, 2005)
The research of legal protections cheque in to banking is regulation of business. In to business buying in trade has persons and rents persons. In the trades is payment cheque and always has persons. This cheque always baying in trade etc. Because in cheque is trades that simple, and not of the risk. In trade a business not payment cash, but not all risk. This cheque blank is letter value that nominal rupiahs, but not nominal rupiahs to payment in trade. Bank is cheque blank no of risk in payment but nominal rupiahs is enough.